2015
DOI: 10.1371/journal.pone.0139370
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Green Tea and (–)-Epigallocatechin Gallate on Transport by OATP1B1, OATP1B3, OCT1, OCT2, MATE1, MATE2-K and P-Glycoprotein

Abstract: Green tea catechins inhibit the function of organic anion transporting polypeptides (OATPs) that mediate the uptake of a diverse group of drugs and endogenous compounds into cells. The present study was aimed at investigating the effect of green tea and its most abundant catechin epigallocatechin gallate (EGCG) on the transport activity of several drug transporters expressed in enterocytes, hepatocytes and renal proximal tubular cells such as OATPs, organic cation transporters (OCTs), multidrug and toxin extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 29 publications
0
50
0
1
Order By: Relevance
“…Based on our in vitro study, inhibition on intestinal or hepatic CYP3A could lead to increased exposure of ticagrelor and declined metabolites, while our in vivo case observed decreased exposure of both parent drug and metabolites, suggesting the potential involvement of other mechanisms in intestinal lumen. Besides the inhibition on enzymes, several reports have shown that the efflux efficiency of P‐gp and intestinal uptake efficiencies of OATP1A2, OATP2B1, organic cation transporter (OCT)1, and OCT2 can also be inhibited by TPE or EGCG in both in vitro and in vivo studies, causing alteration of both parent drug and metabolite (Knop et al., 2015; Misaka et al., 2014; Misaka, Miyazaki, Fukushima, Yamada, & Kimura, 2013). Our preliminary uptake study conducted with Caco‐2 cells confirmed an active uptake behavior of ticagrelor (Figure S1) and then found declined uptake of ticagrelor when cocultured with TPE, EGCG, or ECG, which was comparable to positive inhibitor rifamycin SV (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our in vitro study, inhibition on intestinal or hepatic CYP3A could lead to increased exposure of ticagrelor and declined metabolites, while our in vivo case observed decreased exposure of both parent drug and metabolites, suggesting the potential involvement of other mechanisms in intestinal lumen. Besides the inhibition on enzymes, several reports have shown that the efflux efficiency of P‐gp and intestinal uptake efficiencies of OATP1A2, OATP2B1, organic cation transporter (OCT)1, and OCT2 can also be inhibited by TPE or EGCG in both in vitro and in vivo studies, causing alteration of both parent drug and metabolite (Knop et al., 2015; Misaka et al., 2014; Misaka, Miyazaki, Fukushima, Yamada, & Kimura, 2013). Our preliminary uptake study conducted with Caco‐2 cells confirmed an active uptake behavior of ticagrelor (Figure S1) and then found declined uptake of ticagrelor when cocultured with TPE, EGCG, or ECG, which was comparable to positive inhibitor rifamycin SV (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the widespread and regular use of green tea and its cardiovascular benefits, concurrent use with ticagrelor among ACS patients receiving single or dual antiplatelet therapy is essentially unavoidable, but few studies have been performed. Studies have indicated that TPs or the four catechins exerted moderate to strong inhibitory effects on metabolic enzymes (cytochrome [CYP] P450 superfamily and UDP‐glucuronosyltransferase superfamily), as well as uptake and efflux transporters (Knop et al., 2015; Mohamed & Frye, 2011; Mohamed, Tseng, & Frye, 2010; Muto, Fujita, Yamazaki, & Kamataki, 2001; Nishikawa et al., 2004). Hence, in the case of daily use, whether the long‐term exposure of green tea may affect the absorption, distribution, metabolism, and/or excretion of ticagrelor, and potentially cause pharmacodynamic alteration, particularly for those patients with high risk of cardiovascular events, is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that in vitro parameters for OATP1B1/1B3 show high variability between cell lines and between laboratories. For example, the in vitro probe bromosulfophthalein shows higher uptake in OATP1B3‐injected X. laevis oocytes relative to OATP1B1 (uptake ratio = 8.9 and 5.0, respectively), whereas the opposite is true for human embryonic kidney (HEK) 293 cells expressing OATP1B1 and OATP1B3 (uptake ratio = 7.7 and 3.5, respectively). Additionally, there are substrate differences in affinity for both isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on food–drug interactions, green tea polyphenols may affect the expression or activities of drug-metabolizing enzymes and drug transporters [55,56]. It is currently unknown whether green tea consumption will alter the pharmacokinetics and bioavailability of a chemotherapeutic agent in cancer patients.…”
Section: Pharmacokinetic Effect On Chemotherapeutic Agentsmentioning
confidence: 99%